2009
DOI: 10.1007/12_2009_24
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Stars and Cylindrical Brushes

Abstract: This review summarizes recent work in the field of polyelectrolyte stars and cylindrical brushes. Synthesis of anionic and cationic polyelectrolyte stars and cylindrical brushes by different synthetic strategies is introduced. Solution properties such as titration, osmotic pressure, and inter-polyelectrolyte complexes (IPECs) of the stars and brushes are briefly discussed. We also highlight the use of core-shell polyelectrolyte brushes as the template for the preparation of superparamagnetic hybrid cylinders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 155 publications
0
9
0
Order By: Relevance
“…66 The unusual architecture of CPBs gives them some unique properties such as large dimensions of macromolecules, a low entanglement extent, and a lower critical micelle concentration (CMC). 67 It has been shown that CPBs with poly(L-lysine) side chains and sodium dodecylsulfate (SDS) can form complexes with intriguing structures.…”
Section: Assembly Of Cylindrical Polyelectrolyte Brushesmentioning
confidence: 99%
“…66 The unusual architecture of CPBs gives them some unique properties such as large dimensions of macromolecules, a low entanglement extent, and a lower critical micelle concentration (CMC). 67 It has been shown that CPBs with poly(L-lysine) side chains and sodium dodecylsulfate (SDS) can form complexes with intriguing structures.…”
Section: Assembly Of Cylindrical Polyelectrolyte Brushesmentioning
confidence: 99%
“…Well-defined star-shaped poly(acrylic acid) ((PAA N ) X , with N and X indicating the number-average degree of polymerization and the number of arms, respectively) with N = 90 and X = 5 ((PAA 90 ) 5 , M n = 36 900 g mol À1 , Ð = 1.04) and N = 100 and X = 21 ((PAA 100 ) 21 , M n = 161 500 g mol À1 , Ð = 1.02) as well as linear PAA with M n = 36 000 g mol À1 (N = 500, Ð = 1.1) was synthesized and characterized as described elsewhere. 18,20 Low-molecularweight compounds CuSO 4 Á5H 2 O and ethanol (all of the analytical grade) as well as NaOH (0.1 M standard titre solution) were used as received. Distilled water was used as the solvent.…”
Section: Methodsmentioning
confidence: 99%
“…Obviously, star-shaped polyelectrolytes (also referred to as polyelectrolyte stars) [18][19][20] can be used as nanosized containers for the incorporation of metal ions and further as scaffolds in the preparation of metallo-containing NPs with tunable sizes and preferably with controlled size distribution. To the best of our knowledge, however, there are only a few reports on the reduction of metal ions in such systems.…”
Section: Introductionmentioning
confidence: 99%
“…These are essentially molecular brushes, because chains are grafted from a backbone rather like the comb geometry, although significantly more densely. 170,171 They have structural similarities to articular biopolymers such as lubricin 172 or aggrecan, 173,174 which have impressive lubrication and load-bearing properties. Bottlebrushes are not easy to graft from a surface and experiments are currently dominated by polymers grafted to the surface.…”
Section: Bottlebrushesmentioning
confidence: 99%